Implementation of Group and Individual Supervision Techniques, and Its Effect on the Work Motivation and Performance of Teachers at School Organization - Wiyono, Bambang Budi; Widayati, Sulis Peni; Imron, Ali; Bustami, Abdul Latif; Dayati, Umi (Frontiers in Psychology, 2022)
Teachers have a very important role in determining the quality of the teaching-learning process and the students’ learning outcomes. Learning outcomes will optimally be achieved if it is supported by qualified teachers. One way to enhance the teachers' performance is through instructional supervision which can be divided into two techniques, namely group, and individual supervision techniques. Therefore, this study aims to find out the influence of instructional supervision techniques on the work motivation and performance of elementary school teachers. This study was conducted in East Java, Indonesia, and an explanatory research design was used. The sample was taken from 80 elementary school teachers in Malang and Blitar using a multi-stage random sampling technique. Data were collected through the use of questionnaires and documentation, and then they were analysed by using the structural equation modeling technique. The result of this study showed that group supervision has a significant effect on teachers’ performance, whereas individual supervision influenced teachers’ work motivation and it affected their performance.